Principles of Igneous and Metamorphic Petrology - Winter, John D. (Delhi: Pearson, 2010)
Principles Of Igneous And Metamorphic Petrology is considered an essential companion for a student of geology. Featuring an approach in which techniques are first presented and then applied to assess a field area, readers of this book will be well-equipped to expand the techniques according to the field examples.
Appendix A-B 683-692p.; Index 693-702p.
Keywords: Magma diversity; Metamorphic fluids; Thermodynamics